RenÃ© Sand (1877-1953) and His Contribution to International Social Work, IASSW-President 1946 - 1953 - Kerstin Eilers (Social Work and Society)
The extraordinary significance of the life and work of RenÃ© Sand lies in his central position as a mediator, promoter and coordinator of social work on an increasingly international level during the interwar-period and it can hardly be overestimated. To approach the achievements of Sand's life and work you have to work archaeologically as he does not seem to have left any traces in the literature on social history. In Germany, even within the field of social work his name is hardly known. His biographical sketch and his importance for the development of the profession of social work have fallen into oblivion.